2007
DOI: 10.1016/j.vetmic.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of porcine sapoviruses

Abstract: Sapoviruses (SaVs) within the Caliciviridae family are an important cause of gastroenteritis in both humans and animals. Although the widespread occurrence of divergent human SaV strains has been reported, there have only been a few studies of porcine SaVs examining their genetic diversity. The aim of this study was to assess the genetic diversity of porcine SaVs in piglets with diarrhea in South Korea. Two hundred and thirty-seven fecal specimens from piglets with diarrhea were examined from 78 farms over a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…The primers used and the selection of samples tested by the age and the state of health of the pigs also differed in those studies, making direct comparisons of the results of the different studies difficult, but it can be concluded that sapovirus infection in pigs is common. However, our data confirm that pigs are infected with sapoviruses early in life, a finding that is in line with the findings of studies performed in Venezuela, Brazil, South Korea, and the United States (1,9,16,26). As also described in the papers from Venezuela, Brazil, and Belgium (17), we found sapoviruses in nearly equal numbers in pigs with and without diarrhea as well.…”
Section: Discussionsupporting
confidence: 92%
“…The primers used and the selection of samples tested by the age and the state of health of the pigs also differed in those studies, making direct comparisons of the results of the different studies difficult, but it can be concluded that sapovirus infection in pigs is common. However, our data confirm that pigs are infected with sapoviruses early in life, a finding that is in line with the findings of studies performed in Venezuela, Brazil, South Korea, and the United States (1,9,16,26). As also described in the papers from Venezuela, Brazil, and Belgium (17), we found sapoviruses in nearly equal numbers in pigs with and without diarrhea as well.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous studies have reported the prevalence rates and the genetic features of porcine NoVs and SaVs in Korea [15,[23][24][25]. The results of phylogenetic analyses of porcine NoVs in Korea revealed that all strains belonged to the typical porcine genotypes, such as GII-21 and GII-23.…”
Section: Introductionmentioning
confidence: 89%
“…Porcine NoVs were detected only in asymptomatic finisher pigs, but porcine SaVs could be identified in both diarrheic and asymptomatic pigs [15,[23][24][25]. Several previous studies have reported the prevalence rates and the genetic features of porcine NoVs and SaVs in Korea [15,[23][24][25].…”
Section: Introductionmentioning
confidence: 92%
“…SaVs are also classified into GI to GV, which are further subdivided into a number of clusters and genotypes, according to the genetic variation of their capsid or RdRp genes (8,16,36,41). GI, GII, GIV, and GV have been detected in humans, while GIII has been detected in swine.…”
mentioning
confidence: 99%